Pengaruh Teknik Relaksasi Lima Jari Terhadap Tingkat Nyeri Pada Pasien Post-Op Fraktur Ekstremitas Atas Di Murni Teguh Memorial Hospital - Hutagaol, Simarimbun Putri Uli; Simatupang, Lenny Lusia (STIKes Murni Teguh, 2025)
Fractures are conditions where bones break, typically due to trauma or physical force. Several factors, such as the strength and angle of the impact, along with the condition of the bones and surrounding soft tissue, determine the type of fracture—whether it is complete or incomplete. Fractures of the upper extremities are often caused by falls with the arms extended backward. Data from the WHO indicates a significant rise in fracture cases, from 13 million individuals in 2008 to 21 million in 2010. This study aims to identify pain levels in patients who undergo upper extremity fracture surgery before and after using the five-finger relaxation technique. A quantitative research method with an experimental design was employed, measuring pain in 12 patients before and after the relaxation intervention. Analysis using the Wilcoxon test yielded a p-value of 0.02 < 0.05, indicating a significant effect of the five-finger relaxation technique on pain reduction. In conclusion, this relaxation technique was found to be effective in decreasing pain levels in patients post upper extremity fracture surgery.